2022
DOI: 10.2147/jir.s375487
|View full text |Cite
|
Sign up to set email alerts
|

Chlorite-Oxidized Oxyamylose (COAM) Has Antibacterial Activity and Positively Affects Skin Wound Healing

Abstract: Purpose To verify the antibacterial and immunomodulatory effects of the amylose derivative – chlorite-oxidized oxyamylose (COAM) – in a skin wound setting. Methods In vitro antibacterial effects of COAM against opportunistic bacterial pathogens common to skin wounds, including Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA), were determined by cultivation methods. The effects of COAM on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…128,129 Pereira et al created a fibrin-based hydrogel containing fibrinogen, thrombin and factor XIII to modulate immune cells and molecules in skin wound healing. 130 The results showed that the hydrogel decreased neutrophils and increased non-classical Ly6Clow monocyte and resolutive macrophage (CD206+ and CX3CR1+) populations, and promoted keratinocyte migration, which accelerated mouse defect skin wound healing.…”
Section: Protein-based Immunomodulatory Hydrogelsmentioning
confidence: 96%
“…128,129 Pereira et al created a fibrin-based hydrogel containing fibrinogen, thrombin and factor XIII to modulate immune cells and molecules in skin wound healing. 130 The results showed that the hydrogel decreased neutrophils and increased non-classical Ly6Clow monocyte and resolutive macrophage (CD206+ and CX3CR1+) populations, and promoted keratinocyte migration, which accelerated mouse defect skin wound healing.…”
Section: Protein-based Immunomodulatory Hydrogelsmentioning
confidence: 96%